Anatomical study of nutrient foramen in lower limb dry long bones - Mahat, Samyog; Shrestha, Shamsher; Yadav, Prabhakar (International Journal of Research in Medical Sciences, 2021)
Background: Nutrient artery gain access through nutrient foramen and provide vascular supply to bone. Number, size and location of nutrient foramen has significant medical as well as surgical importance. Any insult to nutrient artery during surgical procedure or during trauma may lead to devascualarization or poor prognosis. Methods: The present study consist of 50 femurs, 50 tibia and 50 fibula, collected from department of anatomy, BPKIHS. Mean length of bone, number, position and size and foraminal index of nutrient foramen was observed and recorded accordingly. Results: In femur 62% bone shows single nutrient foramen. Nutrient foramen was commonly located in medial lip of linea aspera and in upper third of bone which was noted in 80% of bone. In tibia 82% of total bone shows single foramen with absent of foramen in 6% bone. Foramen was commonly located above the soleal line and middle third of bone which was noted in 56% of bone. In fibula 6% of total bone shows absent of nutrient foramen and majority of bone shows single nutrient foramen (82%). Foramen was commonly located in lower part of posterior surface (60%) and in middle third of bone. Conclusions: This study provides details topographic knowledge about nutrient foramen which is important clinically for proper planning of surgery and its outcome.